If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-8 + 6x) = -142 (-8 * 7 + 6x * 7) = -142 (-56 + 42x) = -142 Solving -56 + 42x = -142 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 42x = -142 + 56 Combine like terms: -56 + 56 = 0 0 + 42x = -142 + 56 42x = -142 + 56 Combine like terms: -142 + 56 = -86 42x = -86 Divide each side by '42'. x = -2.047619048 Simplifying x = -2.047619048
| 12v^2-13v=35 | | -(5x+8)+12=24 | | (3*3)-2(11-8)(11-8)=36x | | 3(x+2)+5+x=6(x+3)-2x-7 | | -(9-7c)= | | 5(c+0.8)+6=50 | | 4x^2-15x-54=0 | | -5Y+11=-4(2Y+4) | | -5-9=3w+7 | | -(20+d)= | | 2-x=15-x | | x^4-4x^2+2=0 | | -3x^2+8x=5 | | (n+1)(n+9)=0 | | 15x+4=13x+14 | | 5x^2-30x=0 | | -4.4s-2=-5.5s-42 | | 13+8(5x-9)=2 | | 4m+5=11+6 | | -4(10+4x)=-216 | | 7f=3f-52 | | -z+4z=-3z-4+8z | | 8(x+4)=52 | | 15h-9-6h=9 | | -5(-4-2x)=-70 | | t^2=9 | | 2(5-x)=26 | | 3(2w-1)-4w=27 | | 15x+15=12x-24 | | 63=9(x+3) | | 495=LWH | | 42+9c=16c |